Best Paper Selection (Yearbook of Medical Informatics, 2018)
Bender JL, Cyr AB, Arbuckle L, Ferris LE. Ethics and Privacy Implications of Using the Internet and Social Media to Recruit Participants for Health Research: A Privacy-by-Design Framework for Online Recruitment. J Med Internet Res 2017 Apr 6;19(4):e104 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/28385682/Sanderson SC, Brothers KB, Mercaldo ND, Clayton EW, Antommaria AHM, Aufox SA, Brilliant MH, Campos D, Carrell DS, Connolly J, Conway P, Fullerton SM, Garrison NA, Horowitz CR, Jarvik GP, Kaufman D, Kitchner TE, Li R, Ludman EJ, McCarty CA, McCormick JB, McManus VD, Myers MF, Scrol A, Williams JL, Shrubsole MJ, Schildcrout JS, Smith ME, Holm IA. Public Attitudes toward Consent and Data Sharing in Biobank Research: A Large Multi-site Experimental Survey in the US. Am J Hum Genet 2017 Mar 2;100(3):414-27 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/28190457/Peacock S, Reddy A, Leveille SG, Walker J, Payne TH, Oster NV, Elmore JG. Patient portals and personal health information online: perception, access, and use by US adults. J Am Med Inform Assoc 2017 Apr 1;24(e1):e173-e177 https://academic.oup.com/jamia/article-lookup/doi/10.1093/jamia/ocw095Walker DM, Johnson T, Ford EW, Huerta TR. Trust Me, I'm a Doctor: Examining Changes in How Privacy Concerns Affect Patient Withholding Behavior. J Med Internet Res 2017 Jan 4;19(1):e2 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/28052843/